Barriers to Urban Food Production: Perspectives of Urban Food Producers - Kumudu P. P. Kopiyawattage; Laura A. Warner; Grady T. Roberts (Journal of International Agricultural and Extension Education, 2019)
Locally grown food systems in urban areas is globally important for numerous reasons such as food security, nutrition, financial well-being, and solutions to the many complex issues observed in areas with increasing populations. An understanding of the barriers to urban food production is needed because, if not addressed properly, they may lead to severe threats in urban communities such as food insecurity and poverty. The purpose of this qualitative study was to identify the barriers associated with urban food production. Semi-structured interviews were conducted in Columbus, Ohio, U.S.A. to collect data. Rules and regulations from city ordinances were perceived as the greatest barrier to urban food production. Negative perception towards farming, lack of marketing options, and resource scarcity were also identified as strong barriers to urban food production. Revisiting city ordinances, creating more market options for urban food producers, and directing programs, networks, organizations, and responsible people towards urban farming are recommended to eliminate barriers to urban food production. International agricultural and extension educators may consult the barriers identified in this study and use the findings as a starting point from which to support urban food production.
Keywords: urban extension; urban food production; food production barriers